Sense amplifier offset voltage analysis for both time-zero and time-dependent variability. (August 2019) - Agbo, Innocent; Taouil, Mottaqiallah; Kraak, Daniël; Hamdioui, Said; Weckx, Pieter; Cosemans, Stefan; Raghavan, Praveen; Catthoor, Francky; Dehaene, Wim
Abstract: This paper presents an accurate technique to extensively analyze the impact of time-zero (i.e., global and local variation) and time-dependent (i.e., voltage, temperature, workload, and aging) variation on the offset voltage specification of a memory sense amplifier design using 45 nm predictive technology model (PTM) high performance library. The results show that increasing the supply voltage both for time-zero and time-dependent reduces the offset voltage specification marginally, irrespective of the process corners. In contrast, the offset voltage specification is very sensitive to the temperature and the workload, i.e., the applied voltage patterns. The results also show that a balanced workload results in a significantly lower offset voltage specification. The above results can be used to estimate the required offset voltage accurately for a given lifetime, and operational conditions such as workload, temperature, and voltage; hence, enable the designer to take appropriate measures for a high quality, robust, optimal and reliable design.